Impact of denoising on precision and accuracy of saturation‐recovery‐based myocardial T1 mapping. Issue 5 (4th April 2017) - Bustin, Aurélien; Ferry, Pauline; Codreanu, Andrei; Beaumont, Marine; Liu, Shufang; Burschka, Darius; Felblinger, Jacques; Brau, Anja C.S.; Menini, Anne; Odille, Freddy
Abstract : Purpose: To evaluate the impact of a novel postprocessing denoising technique on accuracy and precision in myocardial T1 mapping. Materials and Methods: This study introduces a fast and robust denoising method developed for magnetic resonance T1 mapping. The technique imposes edge‐preserving regularity and exploits the co‐occurence of spatial gradients in the acquired T1 ‐weighted images. The proposed approach was assessed in simulations, ex vivo data and in vivo imaging on a cohort of 16 healthy volunteers (12 males, average age 39 ± 8 years, 62 ± 9 bpm) both in pre‐ and postcontrast injection. The method was evaluated in myocardial T1 mapping at 3T with a saturation‐recovery technique that is accurate but sensitive to noise. ROIs in the myocardium and left‐ventricle blood pool were analyzed by an experienced reader. Mean T1 values and standard deviation were extracted and compared in all studies. Results: Simulations on synthetic phantom showed signal‐to‐noise ratio and sharpness improvement with the proposed method in comparison with conventional denoising. In vivo results demonstrated that our method preserves accuracy, as no difference in mean T1 values was observed in the myocardium (precontrast: 1433/1426 msec, 95%CI: [−40.7, 55.9], p = 0.75, postcontrast: 766/759 msec, 95%CI: [−60.7, 77.2], p = 0.8). Meanwhile, precision was improved with standard deviations of T1 values being significantly decreased (precontrast: 223/151 msec, 95%CI: [27.3, 116.5], p = 0.003, postcontrast: 176/135 msec, 95%CI: [5.5, 77.1], p = 0.03). Conclusion: The proposed denoising method preserves accuracy and improves precision in myocardial T1 mapping, with the potential to offer better map visualization and analysis. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1377–1388.